Simulation, Aufbau und Charakterisierung von autostereoskopischen Display-Systemen im Fahrzeugbereich - Werner, Tobias (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2017)
In order to extend the functionality of head-up displays as an ergonomic driver assistance system an autostereoscopic approach is investigated. Thereby, depth perception is gained by the fusion of two separated images. Adapted simulation methods are developed and used as a basis for the optical design process. Different technological concepts are developed, analyzed in simulation, as well as realized and characterized in prototypical setups.